2004
DOI: 10.1177/1082013204042067
|View full text |Cite
|
Sign up to set email alerts
|

Use of Response Surface Methodology to Optimize Gluten-Free Bread Fortified with Soy Flour and Dry Milk

Abstract: The percentages of soy flour (X1) and dry milk (X2) were varied for the production of gluten-free bread to optimize batter softness (Y1), specific volume (Y2), crumb grain score (Y3), bread score (Y4) and bread protein content (Y5). A central composite design was used and second-order models for Y1 were employed to generate response surfaces. When bread protein content was decreased from 10 to 3%, specific volume increased from 3.2 to 4.6 cm3/g and bread score increased too. Nevertheless, the highest crumb gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 3 publications
2
45
0
4
Order By: Relevance
“…Moreover, some health benefits are attributed to soy products, like the decrease of the risk for coronary heart disease associated to the consumption of soy protein due to the reduction in total lowdensity lipoprotein cholesterol and also in triacylglycerols [20]. However, high levels of soybean flour may lead to a decrease in the specific volume and sensory properties of the bread [21]. Also a negative effect of high levels of soybean in wheat bread quality has been reported [22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some health benefits are attributed to soy products, like the decrease of the risk for coronary heart disease associated to the consumption of soy protein due to the reduction in total lowdensity lipoprotein cholesterol and also in triacylglycerols [20]. However, high levels of soybean flour may lead to a decrease in the specific volume and sensory properties of the bread [21]. Also a negative effect of high levels of soybean in wheat bread quality has been reported [22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez et al [26], working with soy flour and milk powder in variable amounts, found that a gluten-free bread can be prepared incorporating 7.5% of soy flour and 7.8% of milk powder, thus increasing its protein content from 1% to 7.3% with a minimum alteration of its sensory characteristics.…”
Section: Dairy Productsmentioning
confidence: 99%
“…Once the disease has been diagnosed, the treatment consists in abandoning the consumption of wheat, oat, barley and rye (TACC, in Spanish) for the rest of one's life; that is, a diet based on TACC-free, or "gluten-free" food, must be adopted [23]- [26]. Nowadays, some researchers have raised the idea whether the gluten-free diet for celiac patients should be lifetime, for which adult celiac patients, to whom the disease had been detected during childhood, were evaluated, to study if a lag period of the disease could occur with a normal diet.…”
Section: Introduction To Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…RSM permits the optimization of the formulation and processing conditions. For example, RSM has been used to improve the formulation of a traditional cassava cake, optimize the acceptability of new desserts, and optimize the dehydration of carrot chips with vacuum frying Sanchez et al 2004;Villegas et al 2010;Fan et al 2005). RSM explores the relationships between several variables and one or more responses, permitting the selection of an adequate combination of conditions to achieve a desired response.…”
Section: Introductionmentioning
confidence: 99%